Henry Sewall papers - Sewall, Henry, 1752-1845.
Muster roll with certification (1778 February 16) kept by Sewall for Jacob Allen's company of the 1st Massachusetts Regiment. A journal extract (1783 June 1-25) concerning the activities and movements of the 2nd Massachusetts Regiment at Newburgh, N.Y., the furloughing of soldiers, pay received, and the settlement of personal accounts contains references to Gen. Benjamin Lincoln, Gen. William Heath, and the Society of the Cincinnati.
Microfilm edition of journal extract available
Microfilm produced from original journal extract in the Manuscript Division.
Revolutionary soldier and aide-de-camp to Gen. William Heath.
Collection material in English.
Forms part of: Miscellaneous Manuscripts Collection.
Muster roll was previously cataloged separately.
Keywords: Allen, Jacob, -- active 1778.; Lincoln, Benjamin, -- 1733-1810.; Heath, William, -- 1737-1814.; United States. -- Continental Army. -- Massachusetts Infantry Regiment, 1st (1777-1783); United States. -- Continental Army. -- Massachusetts Infantry Regiment, 2nd (1777-1783); Society of the Cincinnati; New York (State) -- History -- Revolution, 1775-1783.; Newburgh (N.Y.) -- History; Massachusetts -- History -- Revolution, 1775-1783.; New York (State) -- History -- Revolution, 1775-1783.; United States -- History -- Revolution, 1775-1783 -- Campaigns; Soldiers